Penile and generalised calciphylaxis in peritoneal dialysis. (16th April 2015) - Sarkis, Edmond
Abstract : This is a rare case of penile and generalised calciphylaxis. We describe the case of a patient admitted to our hospital for septic shock and necrotic skin findings, end-stage renal disease on peritoneal dialysis. Skin findings turned out to be calciphyactic lesions. The patient was taken to the operating room for penile debridement and started on antibiotics. He was treated with sodium thiosulfate and switched to haemodialysis. Calciphylaxis is a rare disease in which the treatment is basically supportive. Further studies are needed to identify the risk factors, mechanisms of disease and treatment modalities.